Rhetoric vs reality: The disconnect between policy and practice for teachers implementing Aboriginal education in their schools - Burgess, Cathie; Lowe, Kevin (Education Policy Analysis Archives, 2022)
In Australia, pervasive deficit representations and positioning of Aboriginal peoples continue to impact on teachers’ capacity to meaningfully embed Aboriginal curriculum and pedagogies into their teaching. This sits within a policy context driven by standardization, competition and market forces focused on closing the gap between Aboriginal and non-Aboriginal student outcomes to address the statistical dissonance caused by Aboriginal underachievement. Our analysis is informed by Bacchi’s (2009) ‘What’s the ‘problem’ represented to be?’ analytical tool. We reveal discourses that position Aboriginal peoples as the ‘problem’ and the effects of these on teacher practice. Using the 2019 Alice Springs (Mparntwe) Education Declaration, which represents a national partisan vision of Australian education, we demonstrate how discourses of community engagement, Reconciliation and data-driven solutions continue to position Aboriginal peoples as incapable, and government as savior. This flags the silencing of Aboriginal peoples’ key concerns of racism, social justice, truth-telling, sovereignty, and treaty, all of which are central to the ongoing fight for voice, reparative justice and recognition. Until these concerns are heard and accounted for in policies, the gap will remain, teachers will continue to struggle to meaningfully engage with Aboriginal and Torres Strait Islander policies and curriculum content and consequently fail Aboriginal aspirations.